The Effect of Financial Reporting Quality on Financing and Investment - Windy Angela; Rilya Aryancana (ETIKONOMI, 2017)
This paper analysis the effect of reporting quality on financing and investment. It is important for us to understand the relation among them in order to prepare Indonesian companies for ASEAN Economic Community in 2015. The study examines the effect of financial reporting quality on financing and investment of 15 Indonesian companies with large market capitalization based on the Standard and Poor’s Rating Services in its first survey of the major corporate credit trends in the Association of Southeast Asian Nations (ASEAN). Those companies may still be under-investing in relation to its regional peers. The results suggest that (1) financial reporting quality has negative effect on financing. (2) financial reporting quality has positive effect on investment among companies with higher likelihood of over-investing and negative effect on investment among those with higher likelihood of under-investing.DOI: 10.15408/etk.v16i1.4600